2017
DOI: 10.5120/ijca2017914249
|View full text |Cite
|
Sign up to set email alerts
|

Robust Feature Extraction on Vibration Data under Deep-Learning Framework: An Application for Fault Identification in Rotary Machines

Abstract: Mechanical failures in rotating machinery (e.g. wind turbines, generators, motor-derives etc.) may result in catastrophic failures. Different mechanical faults induce characteristic vibrations in the equipment structure. Online vibration monitoring helps mitigate catastrophic failures through early detection and identification of underlying mechanical faults. However, extracting characteristic vibration features that improve fault classification performance and are robust to various noises in the vibration sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…They also defined the process of converting a signal to a 2D grayscale image as a way of preprocessing. Further on, Shaheryar et al [ 28 ] explored CNN in fault identification with spectrograms of vibration images previously converted using short time Fourier transform. Specifically, they used a convolutional neural network in combination with an autoencoder network and a fully coupled classification layer to identify the stages of bearing damage on an available dataset.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…They also defined the process of converting a signal to a 2D grayscale image as a way of preprocessing. Further on, Shaheryar et al [ 28 ] explored CNN in fault identification with spectrograms of vibration images previously converted using short time Fourier transform. Specifically, they used a convolutional neural network in combination with an autoencoder network and a fully coupled classification layer to identify the stages of bearing damage on an available dataset.…”
Section: Convolutional Neural Networkmentioning
confidence: 99%
“…An adaptive multi-sensor data fusion method based on Deep Convolutional Neural Networks (DCNN) was proposed for fault diagnosis in gearbox systems [13]. Hybrid-deep model was proposed to diagnose faults in rotary machines [14]. This model consists of multi-channel CNN followed by stack of denoising encoders.…”
Section: Related Workmentioning
confidence: 99%
“…In [220], a locality preserving projection (LPP) was adopted to fuse the deep features, and thus to build a new deep AE method constructed with a denoising autoencoder (DAE) and a contractive autoencoder (CAE) for the enhancement of featurelearning ability with the goal of diagnosing REB faults. A hybrid deep model consisting of a multi-channel CNN followed by a stack of denoising autoencoders (MCNN-SDAE) was developed by A. Shaheryar et al, [221] for fault identification in rotary machines. In the study, these researchers explored the MCNN for unsupervised feature learning on vibration signals and SDAE for extracting vibration features that are robust and invariant to the noises in vibration signals.…”
Section: Ae-based Dnn Approaches For Reb Phmmentioning
confidence: 99%
“…The possibility of the sparse representation FDD [158], [207], [208][209][210][211][212][213][214][215][216][217][218][219], [221][222][223][224][225] Fault prognosis [220] pros and cons of these SL-based REB PHM, and DL-based REB PHM methods, and their advancements and applications were reviewed and summarized. From this survey study, several key points can be concluded, including:…”
Section: Rbmsmentioning
confidence: 99%